Transcranial Doppler ultrasonography to evaluate cerebral hemodynamic changes in neurocysticercosis - Sanchez-Boluarte, Sofia S.; Barrientos-Iman, Danny M.; Ramirez-Quiñones, Jorge; Bustos, Javier; Ecos, Rosa; Gonzales, Isidro; Saavedra, Herbert; Garcia, Hector H. (Arquivos de Neuro-Psiquiatria, 2024)
Background Arteritis is a complication of neurocysticercosis (NCC), which is not well known and could trigger strokes. The transcranial Doppler ultrasound (TCD) is a noninvasive method for detecting, staging, and monitoring cerebrovascular diseases. Nonetheless, the utility of TCD to evaluate cerebral hemodynamic changes, suggesting vasculitis associated with NCC remains uncertain.Objective To evaluate cerebral hemodynamic changes using TCD in patients with subarachnoid and parenchymal NCC.Methods There were 53 patients with NCC evaluated at a reference hospital for neurological diseases included (29 with subarachnoid and 24 with parenchymal). Participants underwent a clinical interview and serology for cysticercosis and underwent TCD performed within 2 weeks of enrollment. Mean flow velocity, peak systolic velocity, end diastolic velocity, and pulsatility index were recorded.Results Among the participants, there were 23 (43.4%) women, with a median age of 37 years (IQR: 29–48). Cerebral hemodynamic changes suggesting vasculitis were detected in 12 patients (22.64%); the most compromised vessel was the middle cerebral artery in 11 (91.67%) patients. There were more females in the group with sonographic signs of vasculitis (10/12, 83.33% vs. 13/41, 31.71%; p = 0.002), and this was more frequent in the subarachnoid NCC group (9/29, 31.03% vs. 3/24, 12.5%; p = 0.187), although this difference did not reach statistical significance.Conclusion Cerebral hemodynamic changes suggestive of vasculitis are frequent in patients with NCC and can be evaluated using TCD.
Keywords: Neurocysticercosis; Cysticercosis; Ultrasonography, Doppler, Transcranial; Stroke; Vasculitis